Combined effects of high hydrostatic pressure and dispersed oil on the metabolism and the mortality of turbot hepatocytes (Scophthalmus maximus). (June 2020) - Theron, Michaël; Marziou, Alexandra; Pichavant-Rafini, Karine; Le Floch, Stéphane; Lemaire, Philippe; Dussauze, Matthieu
Abstract: Since the DeepWater Horizon oil spill and the use at 1450 m depth of dispersant as a technical response, the need of relevant ecotoxicological data on deep-sea ecosystems becomes crucial. In this context, this study focused on the effect of high hydrostatic pressure (10.1 MPa) on turbot hepatocytes isolated from fish exposed either to chemically dispersed oil, mechanically dispersed oil or dispersant alone. Potential combined effects of oil/dispersant and hydrostatic pressure, were assessed on cell mortality (total cell death, necrosis and apoptosis), cell viability and on hepatocyte oxygen consumption (MO2 ). No change in cell mortality was observed in any of the experimental conditions, whereas, the results of cell viability showed a strong and significant increase in the two oil groups independently of the pressure exposure. Finally, oil exposure and hydrostatic pressure have additive effects on oxygen consumption at a cellular level. Presence of dispersant prevent any MO2 increase in our experimental conditions. These mechanistic effects leading to this increased energetic demand and its eventual inhibition by dispersant must be investigated in further experiments. Highlights: To analyze the effect of high hydrostatic pressure (10.1 MPa) on hepatocytes isolated from turbot exposed to oil compounds. Oil and hydrostatic pressure exposure had additive effects on hepatocyte energetic demand. Dispersant could prevented the increase of oxygen consumption by affecting the mitochondrial energy production.